(Des)integração do Rio São Francisco: remoções e reassentamentos no Cariri Cearense - Viana, Vitor Vasconcelos (2024)
This dissertation begins with a reflection on the transformations in socio- spatial structures caused by the São Francisco River Integration Project withthe Northern Northeast Hydrographic Basins (PISF) in Cariri, Ceará, specifically removals and resettlement. The validated hypothesis of thisresearch was that the PISF implementation process produced a fragmentationin the socio-spatial structures of the directly impacted population, constitutinga new form of coexistence with the territory. The general objectiveistoanalyze the impacts directly linked to the removals caused by the works, aswell as to investigate the compensatory solutions adopted for the communitiesdirectly affected based on the bibliographic review, documentary analysisandcase study organized into three chapters, in addition to the introductionandconclusion. Initially, the PISF is presented and characterized as an instrument of regional development in order to understand it as an element of theproductive restructuring of the Northeast. From this, the changes in socio- spatial structures resulting from its implementation in the regional dimension, linked to removals, are analyzed, evaluating their adversities and benefits. Finally, we understand the territorial solutions and changes that occurredinVila Produtiva Rural de Vassouras in Brejo Santo, Ceará, investigatingtheterritorial impacts of resettlement actions. The theoretical conceptual pillarsare Productive Restructuring, Public Arena and Participation. The mainresult achieved in the research points out that the PISF does not represent aneconomic productive restructuring at the municipal level, but its resettlement program contributed to the territorial restructuring process of the municipality.